Strategy to increase selling price of organic Toraja Arabica coffee at farmers levels in International Markets. Issue 1 (March 2020) - Musa, Y; Darma, R; Panggabean, Y B S
Abstract: Arabica coffee owned by Toraja especially North Toraja is very distinctive with the aroma and flavor produced so that it becomes its own attraction in the hearts of coffee enthusiasts everywhere. But behind the taste and aroma that is very unique there are many problems faced by Arabica coffee farmers in Toraja in particular. This study aims to analyze the potential of North Toraja Arabica coffee agribusiness, which is then followed by studying the benefits that can be done by using the concept of organic farmers to create an appropriate strategy to improve quality in Arabica coffee agribusiness competition. Data taken using observations and direct interviews in the form of a questionnaire to farmers that includes how much can be produced each harvest season, and the price received each sell the harvest to collectors, companies, and several parties who participated in this research. Primary data used in this study are quantitative and qualitative data. The results of this study indicate that the Arabica coffee owned by Toraja has the potential, farmers as producers have a very big role in improving the performance of Arabica coffee development programs. However, observations show that policies in developing human resources in rural areas, especially in terms of farmers' quality and skills, are relatively not working as expected. To reduce the level of dependence of farmers to traders, it is necessary to strive for financial institutions that are able to provide capital needs to farmers in a fast time without complicated procedures. Therefore farmers have alternatives to choose marketing channels that can provide better prices.